Old school - Kinney, Jeff (Puffin London, 2015)
General fiction (children's / teenage). Get ready, book 10 in the phenomenally bestselling Diary of a Wimpy Kid series is coming! Life was better in the old days. Or was it? That's the question Greg Heffley is asking as his town voluntarily unplugs and goes electronics-free. But modern life has its conveniences, and Greg isn't cut out for an old-fashioned world. With tension building inside and outside the Heffley home, will Greg find a way to survive? Or is going 'old school' just too hard for a kid like Greg Praise for Jeff Kinney : "The world has gone crazy for Jeff Kinney's Diary of a Wimpy Kid." (Sun). "Kinney is right up there with J K Rowling as one of the bestselling children's authors on the planet." (Independent). "The most hotly anticipated children's book of the year is here- Diary of a Wimpy Kid." (Big Issue). Ages 9+